2021
DOI: 10.1016/j.jclepro.2020.124729
|View full text |Cite
|
Sign up to set email alerts
|

Energy trilemma based prioritization of waste-to-energy technologies: Implications for post-COVID-19 green economic recovery in Pakistan

Abstract: As lockdown eases, economic activities resume in Pakistan. If the country continues to follow business-as-usual (BAU) then it is anticipated that carbon output could surge past pre-COVID-19 levels – that means more disasters in future. Thus, it is an unprecedented opportunity to shift from BAU and achieve carbon-neutral and nature-positive economic recovery – green economic recovery (GER). To fuel the GER, access to modern, equitable, affordable and sustainable energy is paramount. This study explores waste-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…The lockdown initiatives have led people to an increased learning process in managing food transactions, and while potentially indirectly, a new understanding of responsible consumption has occurred (Aldaco et al 2020). Contrastingly, Shah et al (2020) argued that if the post-COVID-19 world returns to the business-as-usual, it will eliminate the temporary low-emissions transition phase. Therefore, they suggested that the introduction and intensive implementation of waste-to-energy technologies would not only permanently reduce environmental pollution but also, it would put the post-COVID-19 world on a path of sustainable revival in the long-run.…”
Section: Discussionmentioning
confidence: 99%
“…The lockdown initiatives have led people to an increased learning process in managing food transactions, and while potentially indirectly, a new understanding of responsible consumption has occurred (Aldaco et al 2020). Contrastingly, Shah et al (2020) argued that if the post-COVID-19 world returns to the business-as-usual, it will eliminate the temporary low-emissions transition phase. Therefore, they suggested that the introduction and intensive implementation of waste-to-energy technologies would not only permanently reduce environmental pollution but also, it would put the post-COVID-19 world on a path of sustainable revival in the long-run.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a few have investigated the indirect environmental effects of the COVID-19 pandemic [ 5 , 15 ]. Others have explored and debated post-pandemic behaviors [ 17 , 18 ]. However, studies assessing public willingness to wear (WTW) face masks in response to the COVID-19 outbreak are scarce and have been conducted mostly in western parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts are needed to reach a zero-waste economy. It can be obtained through innovative technologies to reduce waste streams, increasing recycling rates, transforming W2E without relying on incineration (Ali Shah et al 2020 ). Shared and Circular Economy Promotion I94 The concept of a shared and circular economy has got attention all over the globe.…”
Section: Proposed Criteria Sub-criteria and Alternative Strategies mentioning
confidence: 99%